PENYULUHAN DAN PELATIHAN TENTANG PIJAT BAYI PADA KADER POSYANDU BALITA DI DESA SIBANG GEDE BADUNG - Parwati, Ni Wayan Manik; Wulandari, Idah Ayu; Haryati, Ni Putu Sri (Jurnal Abdimas ITEKES, 2022)
Posyandu is the spearhead of maternal and child health services in the community. The success of the posyandu cannot be separated from the hard work of cadres who voluntarily manage the posyandu in their respective areas. Lack of training and coaching to improve adequate skills for cadres causes a lack of understanding of cadres' duties, weak information and lack of coordination between officers and cadres in the implementation of posyandu activities. The method used to solve these problems is to increase the knowledge and skills of posyandu cadres about toddler health by providing health education and baby massage training to the cadres. The implementation of counseling activities and baby massage training was carried out at the Sibang Gede Village office with participants from Posyandu cadres from 13 Banjar. To measure changes in knowledge, pre and post tests were carried out. Delivery of extension materials through videos, PPT and check lists. Meanwhile, to improve the skills of Posyandu cadres by practicing baby massage. The results of the pre test showed that 23.07% of respondents had good knowledge, 76.93% had sufficient knowledge. The results of the post test showed that 92.3% of respondents had good knowledge, and 7.7% had sufficient knowledge. With the increased knowledge and skills of posyandu cadres, it is hoped that the cadres can provide information and teach mothers about baby massage in their respective areas.